On the role of crack tip creep deformation in hot compressive dwell fatigue crack growth acceleration in aluminum and nickel engine alloys. (April 2021) - Chen, Xiang; Pettit, Richard G.; Dudzinski, David; Lados, Diana A.
Highlights: Crack growth acceleration due to hot compressive dwell (HCD) effect was observed. HCD effects were studied on fatigue crack growth in 319 cast Al and Inconel 718. In 319 Al, a creep-based waveform effect was observed at RT with a non-dwell cycle. A physics-based model was refined to predict HCD effects on crack growth behavior. Good agreement was found between model predictions and experimental results. Abstract: Ambient and Hot Compressive Dwell (HCD) fatigue experiments were carried out to understand the effects of HCD on the fatigue crack growth behavior of cast 319 Al and Inconel 718 engine alloys. HCD was found to reduce endurance and increase rates of crack growth at engine service temperatures, while far less crack growth acceleration was found at room temperature. A fracture mechanics-based model was developed, considering tensile residual stress contributions due to compressive creep in order to predict crack growth with HCD. Good agreement was found between predictions and experimental results.